1982
DOI: 10.1017/s0263593300003278
|View full text |Cite
|
Sign up to set email alerts
|

Stratigraphy of a flysch succession: the Ordovician of W Nithsdale, SW Scotland

Abstract: A thick Ordovician marine flysch succession including greywackes, conglomer- ates, siltstones and shales occurs in West Nithsdale in the Northern belt of the Southern Uplands. Five new formations of Caradoc and ?Ashgill age are defined based mainly on petrographical and lithological evidence. The proposed correlation with areas up to 80 km distant to the SW, emphasises the persistent nature of the greywacke formations in the Southern Uplands when traced along strike. It is demonstrated that the main inliers of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
59
0

Year Published

1985
1985
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(60 citation statements)
references
References 11 publications
1
59
0
Order By: Relevance
“…Early Ordovician ophiolite obduction was an extensive phenomenon at the Laurentian margin of Iapetus (Colman-Sadd et al 1992) and the subsequent erosion of the basic and ultrabasic rocks produced widespread late Ordovician greywackes rich in ophiolitic detritus. In the Southern Uplands these occur in the oldest, most northerly tectonostratigraphic tract (Floyd 1982). However, in view of the considerable strike extent of ophiolitic material, the juxtaposition with the Ballantrae Complex across the Southern Upland Fault may be fortuitous and should not be regarded as constraining lateral movement on that structure.…”
Section: The Southern Uplands Terranementioning
confidence: 99%
“…Early Ordovician ophiolite obduction was an extensive phenomenon at the Laurentian margin of Iapetus (Colman-Sadd et al 1992) and the subsequent erosion of the basic and ultrabasic rocks produced widespread late Ordovician greywackes rich in ophiolitic detritus. In the Southern Uplands these occur in the oldest, most northerly tectonostratigraphic tract (Floyd 1982). However, in view of the considerable strike extent of ophiolitic material, the juxtaposition with the Ballantrae Complex across the Southern Upland Fault may be fortuitous and should not be regarded as constraining lateral movement on that structure.…”
Section: The Southern Uplands Terranementioning
confidence: 99%
“…Arc-style debris has been found in the coeval accretionary prisms in both the Southern Uplands (Floyd 1982;Smith et al 2001) and in Ireland (Morris 1987), confirming its former extent. Although the derivation of these deposits is sometimes contentious (Kelley & Bluck 1989;Phillips et al 2003), Kelling et al (1987), taking a considerable dataset, suggested sources mainly from the NW and NE.…”
Section: Later Ordovicianmentioning
confidence: 79%
“…However, re-valuation of the induration and petrography of the matrix (see below), together with the clast content and very high magnetic susceptibility, suggests that the unit is more likely to be a rudaceous facies within the Marchburn Formation (Floyd 1982). We propose that the Lamington Conglomerate Member (LAMN) is an integral part of the Marchburn Formation (MCHB), part of the Tappins Group (TAP).…”
Section: Introductionmentioning
confidence: 91%